Neurosurgical Resident Training in Germany - Stienen, Martin N.; Gempt, Jens; Gautschi, Oliver P.; Demetriades, Andreas K.; Netuka, David; Kuhlen, Dominique E.; Schaller, Karl; Ringel, Florian (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Introduction Efficient neurosurgical training is of paramount importance to provide continuing high-quality medical care to patients. In this era of law-enforced working hour restrictions, however, maintaining high-quality training can be a challenge and requires some restructuring. We evaluated the current status of resident training in Germany.Methods An electronic survey was sent to European neurosurgical trainees between June 2014 and March 2015. The responses of German trainees were compared with those of trainees from other European countries. Logistic regression analysis was performed to assess the effect size of the relationship between a trainee being from Germany and the outcome (e.g., satisfaction, working time).Results Of 532 responses, 95 were from German trainees (17.8%). In a multivariate analysis corrected for baseline group differences, German trainees were 29% as likely as non-German trainees to be satisfied with clinical lectures given at their teaching facility (odds ratio [OR]: 0.29; 95% confidence interval [CI]: 0.18–0.49; p < 0.0001). The satisfaction rate with hands-on operating room exposure was 73.9% and equal to the rate in Europe (OR: 0.94; 95% CI, 0.56–1.59; p = 0.834). German trainees were 2.3 times as likely to perform a lumbar spine intervention as the primary surgeon within the first year of training (OR: 2.27; 95% CI, 1.42–3.64; p = 0.001). However, they were less likely to perform a cervical spine procedure within 24 months of training (OR: 0.38; 95% CI, 0.17–0.82; p = 0.014) and less likely to perform a craniotomy within 36 months of training (OR: 0.49; 95% CI, 0.31–0.79; p = 0.003). Only 25.6% of German trainees currently adhere to the weekly limit of 48 hours as requested from the European Working Time Directive 2003/88/EC, and in an international comparison, German trainees were twice as likely to work > 50 hours per week (OR: 2.13; 95% CI, 1.25–3.61; p = 0.005). This working time, however, is less spent in the operating suite (OR: 0.26; 95% CI, 0.11–0.59; p = 0.001) and more doing administrative work (OR: 1.83; 95% CI, 1.13–2.96; p = 0.015).Conclusion Some theoretical and practical aspects of neurosurgical training are superior, but a considerable proportion of relevant aspects are inferior in Germany compared with other European countries. The present analyses provide the opportunity for a critical review of the local conditions in German training facilities.
Keywords: resident education in Germany; European Working Time Directive; training conditions; satisfaction; neuro surgical training